Structural Transformation in the Indonesian Economy: Why does 'Financial Development' Matter? - Nanga, Muana; Widjaja, William (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
This study offers a comprehensive examination of Indonesia's process of changing its economic structure from 2000 to 2020. Structural transformation, characterized by changes in the distribution of jobs among different sectors, is crucial for fostering economic growth. It emphasizes phenomena such as the decrease in agricultural GDP shares, rural-urban migration and shifts in economic sectors, which resemble the patterns observed in emerging countries. Nevertheless, the rate of employment transformation is comparatively slower than the fluctuations in GDP, suggesting a more gradual and protracted process of structural change. The analysis focuses on obstacles to transformation, such as insufficient personnel and digital infrastructure. The study examines the relationships between structural transformation and economic indicators in the provinces of Indonesia from 2011 to 2022, utilizing panel data regression models. The findings indicate strong correlations between economic development, human capital, financial development, digital technology, and structural transformation. The study highlights the significance of tackling these elements to accelerate transformation. The policy implications of this proposal suggest that Indonesia should prioritize economic and digital growth, improve human capital, and strengthen the financial sector. This will lead to a more rapid and comprehensive structural transformation in the country.